Improvement of the graphical method for plotting the shear and moment diagrams for members subjected to linearly varying loads - Husain, Muhammed Abbas; Ali, Abdulkhaliq Salim (Zielona Góra: Uniwersytet Zielonogórski)
This study presents an improvement of the graphical method for plotting the shear and moment diagrams for the structural members under linearly varying loads (triangular and trapezoidal loads). Based on the parabolic nature of the shear function, when the loading varies linearly, and on the relations among load, shear, and moment, a mathematical equation is developed to locate the zero-shear point, while a geometric technique is presented to calculate the parabolic shear area.
Keywords: shear diagrams; moment diagram; graphical method; improvement; varying loads